Transparansi Pengelolaan Dana Desa Ilili Tahun 2021 Kecamatan Wakate Kabupaten Seram Bagian Timur - Keliangin, Rivai; Banggu, Masni; Sattu, Sattu; Kalagison, Miryam Diana (Jurnal Fase Kemajuan Sosial dan Politik: Faksi, 2024)
The aim of this research is to determine the transparency of the management of the Iriri Village Fund in Wakate District, Eastern Seram Regency in 2021. This research method uses descriptive and analytical qualitative research methods. Observation, interview, and literature review techniques were used for data collection. The informants chosen were those who could answer the research questions. The results of the research show that transparency of financial management in Iriri Village, Wakate District, East Seram Regency in 2021 can be seen at four levels, namely planning, implementation, management and reporting accountability. The village development plan is outlined in the Plan Village Medium Term Development (RPJMD). In its implementation, village funds come from the APBN (State Income and Expenditure Budget). Administration is carried out by the village treasurer by recording income, expenditure and bookkeeping at the end of each month. The village head is obliged to make an accountability report and submit a report on the implementation of the regional income and expenditure budget to the regent/mayor.